2014
DOI: 10.1177/1358863x14536630
|View full text |Cite
|
Sign up to set email alerts
|

The impact of change in physical activity on change in arterial stiffness in overweight or obese sedentary young adults

Abstract: Arterial stiffness is associated with cardiovascular events and mortality. Lifestyle factors such as physical activity may reduce arterial stiffness. The purpose of this study is to determine the impact of change in physical activity (PA) on one-year change in arterial stiffness in 274 overweight/obese sedentary young adults. The Slow Adverse Vascular Effects of excess weight (SAVE) trial was a study evaluating the relationships between weight loss, dietary sodium, and vascular health. PA was measured with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…A study in a middle‐aged, overweight, and diabetic subsample of the Framingham Heart Study third‐generation cohort observed a significant effect of 0.53 m/s lower PWV with every 10min MVPA per day, 31 which is comparable to our results. Another study in healthy middle‐aged individuals with obesity demonstrated a 0.05‐0.38 m/s reduction of baPWV per 8 min/d increase of MVPA in a 12 months intervention 32 . They also observed a reduction of c‐reactive protein as well as improved insulin sensitivity, blood lipid profile, and mean arterial blood pressure.…”
Section: Discussionmentioning
confidence: 90%
“…A study in a middle‐aged, overweight, and diabetic subsample of the Framingham Heart Study third‐generation cohort observed a significant effect of 0.53 m/s lower PWV with every 10min MVPA per day, 31 which is comparable to our results. Another study in healthy middle‐aged individuals with obesity demonstrated a 0.05‐0.38 m/s reduction of baPWV per 8 min/d increase of MVPA in a 12 months intervention 32 . They also observed a reduction of c‐reactive protein as well as improved insulin sensitivity, blood lipid profile, and mean arterial blood pressure.…”
Section: Discussionmentioning
confidence: 90%
“…In a medium sized longitudinal study particularly PA at higher intensity was favorable regarding central and peripheral arterial stiffness in younger persons [14,15]. In the only study analyzing baPWV and PA intensities an increase in moderate-to-vigorous PA, but not light intensity PA, was linked with a decrease of baPWV in 274 overweight and obese young adults longitudinally within one year [20]. In 103 postmenopausal women moderate and vigorous PA was inversely associated with central arterial stiffness [19].…”
Section: Discussionmentioning
confidence: 99%
“…CAVI reflects arterial stiffness of the aorta and the iliac, femoral and tibial arteries [25] and baPWV between the brachial and tibial arteries [29]. Since both of these indices cover different segments of the arterial tree, they reflect a combination of central and peripheral arterial stiffness [20,21].…”
Section: Arterial Stiffness Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in overweight-to-obese adults, a modest increase in physical activity was associated with reduced arterial stiffness, a risk factor of future cardiovascular events [13]. Furthermore, in patients with a diagnosed cardiovascular disease, an inverse association between physical activity and mortality was shown (i.e.…”
mentioning
confidence: 99%